MENYOROTI HAK DAN KEWAJIBAN ASASI MANUSIA DALAM ASPEK EKONOMI (Sebagai Ciri Negara Kesejahteraan (Welfare State)) - Amir, Rahma (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2017)
In Islamic view, common well-being management may not go against syariat Islam. To it, it is not possible in state that setting to terminological syariat Islam, E.g. do floozie localization as arena do adultery or concedes nauseating liquor sell or concedes gambling, since that conduct are prohibited conducts that prohibitted by Syariat Islam. In Islamic view, people is entitled to welfare, and honor bound advance common welfare, smartening up people life, even active deep all life aspect towards well-being all its citizen its state. Maybe no one state even at world it that don't program prosperity in economic area for its citizen. All politician make poverty remove as central issue well while campaign term, and also after as president or governance head. For state already go forward, well-being increasing problem its citizen, must not miss from its parent plan, beside approaching on another areas. But such, trick that sailed through by it can variably at each state.